Prognostic Value of Tumor-Infiltrating Lymphocytes and Tertiary Lymphoid Structures in Epstein-Barr Virus-Associated and -Negative Gastric Carcinoma - Cheng, Na; Li, Peng; Cheng, Huanhuan; Zhao, Xiaoxiao; Dong, Min; Zhang, Yiwang; Zhao, Peizhen; Chen, Jianning; Shao, Chunkui (Frontiers in Immunology, 2021)
Background: Tumor-infiltrating lymphocytes (TILs) are considered a manifestation of the host immune response against cancer and tertiary lymphoid structures (TLS) may contribute to lymphocytes recruitment. Both of them have been reported as potential prognostic parameters in some human malignancies. However, the roles of TILs, TLS and their correlation in Epstein-Barr Virus-associated gastric carcinoma (EBVaGC) and EBV-negative gastric carcinoma (EBVnGC) are largely unknown. Methods: To observe the correlation among TILs, TLS and clinicopathological characteristics and their prognostic significance in EBVaGC and EBVnGC, respectively. TILs and TLS were assessed by morphology and/or immunohistochemistry, and accompanied by clinicopathological analysis from 846 gastric cancer patients in multiple institutions. Results: Forty-two (5.0%) cases of EBVaGC and 804 cases of EBVnGC were identified by in situ hybridization, respectively. For EBVnGC, higher TILs grade was correlated with TLS-present. EBVnGC patients with high TILs grade and TLS-present exhibited survival benefits. TILs (P = 0.001) and TLS (P = 0.003), especially TILs & TLS (P < 0.001) were independent prognostic factors in EBVnGC. A nomogram was constructed and validated for predicting the probability of overall survival and performed well with a good calibration. No significant prognostic value was detected in EBVaGC. Conclusion: TILs and TLS, especially TILs & TLS were promising prognostic indicators for overall survival in EBVnGC. TILs and TLS were highly overlapping in their extent and prognostic abilities, and may be considered as a coindicator of prognosis of gastric cancer. The evaluations of TILs and TLS are simple and can be assessed routinely in pathological diagnosis.